Expression and localization of two β-carbonic anhydrases in Bienertia, a single-cell C4 plant - Nguyen, Tho; Lee, Nakyoung; Frömling, Fabian J.; Meister, Toni L.; Kim, Jung Sun; Offermann, Sascha; Hwang, Inhwan (Frontiers in Plant Science, 2025)
Carbonic anhydrases (CAs) are ubiquitous enzymes that catalyze reversibly both the hydration and dehydration reactions of CO2 and HCO3-, respectively. Higher plants contain many different isoforms of CAs that can be classified into α-, β- and γ-type subfamilies. β-type CAs play a key role in the CO2-concentrating mechanism, thereby contributing to efficient photosynthesis in the C4 plants in addition to many other biochemical reactions in plant metabolism. Here, we characterized at the molecular, cellular and biochemical levels two β-type CAs in Bienertia sinuspersici, a plant that operates a C4 carbon concentrating mechanism within individual cells without the Kranz anatomy. These two β-type CAs (BsCAβs), named BsCAβ1 and BsCAβ2, in Bienertia were strongly induced along with maturation of leaves. Both BsCAβ1 and BsCAβ2 existed as a dimeric form in vivo but showed differential localization. BsCAβ2 was localized exclusively to the plasma membrane in Bienertia and when expressed heterologously in the C3 Arabidopsis. In contrast, BsCAβ1 largely localized to the cytosol together with a portion to the plasma membrane (PM) in both plants. BsCAβ2 had two cysteine residues at the N-terminal region for palmitoylation and their substitution with serine residues led to a change in the localization from the plasma membrane (PM) to the cytosol. Thus, we propose that BsCAβ2 localizes to the PM using a lipid moiety added posttranslationally plays a role in conversion of cytosolic CO2 into HCO3- as part of the CO2-concentrating mechanism, thereby contributing to the single-cell C4 photosynthesis in Bienertia.